Synchronization of Chaotic and Hyperchaotic Nonlinear Dynamical Systems and Their Numerous Applications: A Review - Bora, Riddhi Mohan; Sharma, Bharat Bhushan (Journal of Applied Nonlinear Dynamics, 2026)
Over the last few decades, there has been a growing interest in chaotic systems and their behavior across research communities. Chaotic systems are dependent on initial conditions, meaning that even small variations can lead to vastly different outcomes, making precise prediction difficult. Synchronizing chaotic systems has become an important challenge with a wide range of applications, such as secure communication, robotics, and economics. However, synchronizing non-identical or differently ordered systems presents challenges. In common scenarios, synchronization algorithms and control strategies are derived under ideal conditions, but real-world applications are often affected by experimental uncertainties, external disturbances, and time delays, making control solutions more difficult to implement. As researchers explore the boundaries of this area of study, they have established several observations, including the challenges involved in synchronizing different types of chaotic systems and the importance of developing ways to address measured uncertainties and external disturbances. Overall, the study of chaotic system synchronization offers insights into a natural phenomenon that has broad applications across many disciplines.